Beyond the Usual Suspects: Job Desperation as a Driver of Turnover Intention and Job Search Behaviour - Kertechian, Kevin; El-Farr, Hadi (Relations industrielles / Industrial Relations, 2025)
Workers may experience job desperation, characterized by frustration, pressure to quit and readiness to take extreme steps to secure a new job position. We examined the psychometric properties of a French-language version of the Job Desperation Scale by administering a survey to three independent cohorts of French-speaking employees, with a view to assessing the antecedents of job search behaviour and intention to quit. The first (n = 253) and second (n = 184) cohorts, composed of employees from France and Canada respectively, responded to the survey for the exploratory and confirmatory stages of analysis. The third sample (n = 252) of French employees responded both to the survey and to additional measures that typically identify antecedents of job search behaviour and turnover intention. The findings confirm the single-factor structure and robustness of the French-language version. More importantly, they show the substantial and incremental predictive power of job desperation in explaining job search behaviour and turnover intention. These insights help explain job desperation as a critical factor in contemporary labour markets and contribute to the vocational behaviour literature.